Asking the Right Questions to Ascertain Early Childhood Secondhand Smoke Exposures - Biagini Myers, Jocelyn M. (2012)
Secondhand smoke is associated with a myriad of adverse health outcomes. Therefore, it is essential for clinicians to ask precise questions about exposures, particularly for children. We present 4 questions that incorporate several locations of exposure and provide a more comprehensive account of children’s smoke exposures than maternal smoking alone.